(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Many hormones have been implicated in dry eye syndrome. This study was carried out to investigate the effects of antidiuretic hormone (ADH) on tear secretion. Fifty (50) healthy male and female volunteers between the ages of 21 and 70 years were studied. They were given exogenous ADH in the form of intranasal desmopressin spray (DDAVP). Total and basal tear secretions were assessed using the Schirmer strip at baseline and at 30 minutes intervals for a period of 180 minutes after the nasal administration of 10 μg desmopressin spray into each nostril. Blood samples were taken before and 60 minutes after desmopressin administration for the determination of plasma osmolality and plasma ADH concentrations. Results showed a significant reduction (p<0.001) in the means of total and basal tear secretions from baselines of 20.04 ± 1.19 and 14.64 ± 1.00 mm/5mins to 12.80 ± 0.75 and 9.68 ± 0.72 mm/5mins peak reductions respectively. The peak reduction was observed at 90 minutes assessment time after desmopressin administration. The difference in mean total tear secretions between males and females were statistically significant (p < 0.05). The difference in mean plasma osmolality before and 60 minutes after desmopressin administration was not statistically significant. However, there was a significant increase (p<0.05) in mean ADH concentration after DDAVP administration. It is concluded from this study that exogenous ADH reduces tear secretion in man with associated increase in ADH concentration but no change in plasma osmolality.